Micro-Foundations of “Doing Well by Doing Good”:Multilevel Effects of Work-Life Policies on EmployeeWell-Being and Sales Growth - Mayo, Margarita; Guillén, Laura; Cao, Jie; Firfiray, Shainaz; Sanchez, Juan I. (Wiley, 2026)
This study unravels how the effects of work-life policies (WLPs) on individual employees' perceived control over their work schedule have cumulative effects across employees, ultimately crossing levels to enhance organizational outcomes like sales. We tested a multilevel mediating model comprising two cross-level mechanisms: a top-down link between the organization's availability of WLPs and individual-level variables like control over work schedule and job satisfaction, and a bottom-up link between job satisfaction (aggregated within the organization) and sales growth. Analyses of multilevel, multisource data from 3262 employees in 70 organizations supported the top–down hypotheses predicting that gains in employee control over their work schedule mediate the positive relationship between WLPs availability and job satisfaction. Furthermore, analyses of sales growth data using a matched subsample of 39 organizations and 1872 employees supported the bottom–up hypothesis that organization-level job satisfaction is positively associated with sales growth over a three-year span. Our results begin to shed light on the micro-foundations of doing well (i.e., increasing sales) by doing good (i.e., increasing employees' control over their work schedules through WLP).
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico; Control over work schedule; employee well-being; job satisfaction; sales growth; work-life policies